FIRST RECORD OF MAXILLARY DENTITION OF POTAMOCHOERUS THEOBALDI (SUIDAE, MAMMALIA) FROM THE UPPER SIWALIKS OF INDIA - SURESH KUMAR; RAJAN GAUR (Rivista Italiana di Paleontologia e Stratigrafia, 2013)
The present paper describes the maxillary dentition of Potamochoerus theobaldi. A well preserved right maxillary fragment with P4-M2 was collected from the Tatrot Formation of the Upper Siwaliks exposed northeast of Khetpurali Village near Raipur Rani (Haryana), Northwest India. The specimen was found associated with several other mammalian taxa, which include Stegodon insignis, Hexaprotodon sivalensis, Camelus sivalensis, Gazella sp., and yet to be identified Bovini. The mammalian faunal assemblage suggests an Early Pliocene age for the Tatrot deposits of Upper Siwaliks in the area. P. theobaldi was probably adapted to a bush land and forest fringe type of habitat. The present discovery is significant in the sense that it represents the first report of the maxillary dentition of Potamochoerus theobaldi from the Indian Siwaliks.